Uso De Los Sensores Remotos En Mediciones Forestales - Vásconez, Norma Lara; Sevilla, Hernán Chamorro (European Scientific Journal, ESJ, 2018)
To understand the use of remote sensors in forestry measurements, some of the most relevant definitions have been taken from a wide variety that currently exist, therefore, we will say that these generally play a predominant role in the Dasometry and that all The forest resource requires qualitative and quantitative information regarding the state of the forest and its evolution over time, with sampling that follows one of the existing methods. Historically, modern discipline arises with the invention of flight and the first photographs are obtained from a balloon in the years 1858 and 1859, in 1909 and on board the airplane the first photographic observation is acquired. The first aerial camera was developed in 1915 by J.T.C. Moore, starting the interesting way forward in the techniques of aerial photography using modified combat aircraft giving way to what was called systematic aerial photography in the late 50s. The development on a global scale of the first artificial satellites, allowed remote sensing in the middle of the 20th century on board the first satellite placed in orbit is that of the TYROS series in 1960 by NASA, becoming the pioneer in missions of meteorological observation, which also led to the appearance of satellite image processing, using mathematical procedures such as the Fourier transform. During the 70s missions were promoted with the objective of exploring the solar system and the moon; giving rise to the first spatial photographs taken by Alan B. Shepard rudimentary, Subsequently, Apollo-9 was used for the first multi-spectral experiment in which 4 Hasselblad cameras with different filters were installed. On July 23, 1972, the Landsat project appeared with the launch of the first satellite of the ERTS series (Earth Resources Technology Satellite). Google Earth in the 21st century, introduces online web services making remote sensing accessible to all audiences, with many techniques and processes that allow an image of the earth’s surface to be obtained remotely captured by remote sensors located on satellites or airplanes that gather the spectral and spatial relations of objects. Interferometric radar synthetic aperture They are used to producing accurate digital models of large areas of land. LiDAR(An acronym for the English Light Detection and Ranging) is a monochrome active sensor, its mode of operation consists of measuring the distance between the sensor and the target. It is less expensive compared to manual inventory is multi-purpose, allows a complete survey of the study area, is more efficient than photogrammetry. The multi-spectral acquisition is based on the collection and analysis of areas or objects that emit or reflect radiation at a higher level than nearby objects. The quality of the information collected remotely, once the correction of errors through georeferencing with the help of specialized programs, will depend on their resolutions: spatial, spectral, radiometric and temporal.